Gallium-based liquid metal lipid lubricant, preparation method and application thereof and lubricating system
By using gallium-based liquid metal grease lubricant, the problem of degradation of lubricating performance of space liquid lubricant under atomic oxygen radiation is solved, and the stability of lubricating performance under irradiation environment is achieved, and the cost-performance ratio is optimized.
Patent Information
- Application Number
- CN202510088186.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Existing space liquid lubricants are prone to chemical bond fracture and oxidation under atomic oxygen radiation, resulting in degradation or failure of lubricating performance, and there is still a risk of deterioration and failure under long-term irradiation.
A gallium-based liquid metal grease lubricant is used, with an elemental composition of 70-72% gallium, 14-16% indium, 12-14% tin and 0.8-1.2% zinc. It is prepared by smelting treatment in a protective atmosphere and stirring in an atmospheric environment to form a lubricant with high viscosity and stability.
Under the spatial atomic oxygen irradiation environment, the gallium-based liquid metal grease lubricant can maintain the friction coefficient and wear rate without significant changes from before irradiation, avoid lubrication failure, and increase zinc while reducing the amount of indium and tin to reduce the melting point, optimizing the cost-performance ratio.
Smart Images

Figure CN119912994A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lubricants, and in particular to a gallium-based liquid metal grease lubricant, a preparation method and application thereof, and a lubrication system. Background Art
[0002] Space liquid lubricants mainly include synthetic lubricants represented by perfluoropolyether, polyalphaolefin, polyalkylated cyclopentane, polysiloxane, etc., which are widely used in spacecraft motion mechanisms. However, the space environment has a significant impact on the performance and life of lubricants. Typical space environmental factors mainly include ultra-high vacuum, solar ultraviolet, atomic oxygen erosion, charged particle irradiation, high and low temperature alternation, debris and dust, etc.
[0003] Atomic oxygen irradiation is a space environment unique to low earth orbit (200-700km). It is generated by the photodissociation of oxygen under the irradiation of solar ultraviolet rays with a wavelength less than 243nm. The relative speed between atomic oxygen and the orbiting spacecraft is 7-8km·s, and the atomic oxygen beam density can reach 10 13 ~10 15 atoms / (cm 2 ·s), the average impact kinetic energy can reach 4-5eV. At the same time, atomic oxygen has a higher chemical activity than molecular oxygen, which can cause the chemical bonds of organic molecules in space lubricating grease to break and oxidize, resulting in a decrease in lubrication performance or even failure.
[0004] At present, there are two main methods for improving the atomic oxygen radiation resistance of space lubricants. One is to change the molecular structure of organic matter in lubricants, modify the CF bond or graft Si-containing components. The bond energy of the CF bond is higher than that of the CC bond and the C-Si bond. Therefore, the molecular structure of the new fluorinated trisilane lubricant with 3,3,3-trifluoropropyl substituent grafted with the CF bond is more stable, and it is not easy to break the bond under the action of atomic oxygen radiation, and has better atomic oxygen radiation resistance (Chemical Letters 2014, 43: 1578-1580). The second is to compound other organic substances that are more prone to bond breaking and oxidation in lubricants. Chinese invention patent CN202311274917.6 compounds modified POSS additives in polyalkylated cyclopentane base oil. The ring structure of the modified POSS additive will break the bond under the action of space atomic oxygen radiation, which can reduce the damage of atomic oxygen radiation to the molecular structure of the base oil, indirectly protect the structural stability of the base oil, and thus play a role in resisting atomic oxygen radiation. Although both methods can slow down the deterioration rate of lubricating grease due to atomic oxygen irradiation, there is still a risk of deterioration and failure under long-term irradiation. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a gallium-based liquid metal grease lubricant and its preparation method and application, and a lubrication system. The gallium-based liquid metal grease lubricant is used in a space atomic oxygen irradiation environment, and the friction coefficient and wear rate of the friction pair will not change significantly compared with before irradiation, that is, it will not fail in a space atomic oxygen irradiation environment.
[0006] The present invention provides a gallium-based liquid metal grease lubricant. The gallium-based liquid metal used to prepare the gallium-based liquid metal grease lubricant comprises, by weight percentage, 70-72% gallium, 14-16% indium, 12-14% tin and 0.8-1.2% zinc.
[0007] The viscosity of the gallium-based liquid metal grease lubricant is ≥6.0×10 6 mPa·s.
[0008] Preferably, in terms of mass percentage, the elements of the gallium-based liquid metal used to prepare the gallium-based liquid metal grease lubricant include 71% gallium, 15% indium, 13% tin and 1% zinc.
[0009] The present invention also provides a method for preparing the gallium-based liquid metal grease lubricant described in the above technical solution, comprising the following steps:
[0010] After mixing the metal elements for preparing the gallium-based liquid metal grease lubricant, smelting the mixture in a protective atmosphere to obtain the gallium-based liquid metal;
[0011] The gallium-based liquid metal is stirred in an atmospheric environment to obtain the gallium-based liquid metal grease lubricant.
[0012] Preferably, the smelting process is carried out in a protective atmosphere;
[0013] The protective atmosphere is argon atmosphere.
[0014] Preferably, the smelting treatment is carried out at a temperature of 500 to 600° C. and for a time of 1.5 to 2 hours.
[0015] Preferably, the stirring speed is 200-600 rpm and the temperature is 20-80°C.
[0016] Preferably, the metal element for preparing the gallium-based liquid metal includes a gallium block, an indium wire with a length of 1 to 3 mm, a tin wire with a length of 1 to 3 mm, and a zinc wire with a length of 1 to 3 mm;
[0017] The purity of the metal element used to prepare the gallium-based liquid metal is greater than 99.99%.
[0018] Preferably, the mixing comprises melting the gallium block and mixing it with an indium wire having a length of 1 to 3 mm, a tin wire having a length of 1 to 3 mm, and a zinc wire having a length of 1 to 3 mm.
[0019] The present invention also provides the use of the gallium-based liquid metal grease lubricant described in the above technical solution or the gallium-based liquid metal grease lubricant prepared by the preparation method described in the above technical solution in the lubrication field of space atomic oxygen irradiation environment.
[0020] The present invention also provides a lubrication system suitable for space atomic oxygen irradiation environment, including a gallium-based liquid metal grease lubricant and a friction pair;
[0021] The material of the friction pair includes an iron-based alloy, a nickel-based alloy or a titanium alloy;
[0022] The gallium-based liquid metal grease lubricant is the gallium-based liquid metal grease lubricant described in the above technical solution or the gallium-based liquid metal grease lubricant prepared by the preparation method described in the above technical solution.
[0023] The present invention also provides a gallium-based liquid metal grease lubricant. The gallium-based liquid metal used to prepare the gallium-based liquid metal grease lubricant comprises, in terms of mass percentage, 70-72% gallium, 14-16% indium, 12-14% tin and 0.8-1.2% zinc. The viscosity of the gallium-based liquid metal grease lubricant is ≥6.0×10 6 mPa·s. Gallium-based liquid metal grease lubricant provides lubrication by adsorbing gallium-rich film on the friction interface during friction, while indium and tin basically do not participate in the friction process; in addition, under the irradiation of atomic oxygen in space, the three elements of gallium, indium and tin, mainly gallium, will oxidize, while indium and tin will precipitate to form solid particles, which will have a certain destructive effect on lubrication; at the same time, the unit price of indium wire with a diameter of 1mm and a purity of 99.99% is 4,500 yuan / kg, the unit price of gallium block with a purity of 99.99% is 4,000 yuan / kg, and the unit price of indium block with a diameter of 1mm and a purity of 99.99% is 4,000 yuan / kg. The unit price of tin wire is 1,300 yuan / kg, and the unit price of zinc wire with a diameter of 1 mm and a purity of 99.99% is 800 yuan / kg. The unit price of indium is relatively high, and the unit prices of tin and zinc are relatively low. Furthermore, since the main function of indium and tin is to reduce the melting point of gallium-based liquid metal, they are indispensable, and the melting point of gallium-based liquid metal with a small amount of zinc element is lower, due to the alternating temperature changes in the near-Earth orbit space environment, lubricants with lower melting points are more suitable for application in this scenario. Therefore, the gallium-based liquid metal described in the present invention is relatively cheaper than conventional gallium-based liquid metal (Ga 75.5 In 24.5 (wt.%) binary eutectic alloy and Ga 68.5 In 21.5 Sn10 (wt.%) ternary eutectic alloy), reducing the amount of indium, increasing the amount of tin, and adding zinc (to lower the melting point), taking into account both the lubrication performance and the cost issue; further, the gallium-based liquid metal is stirred in the air to obtain a grease-like lubricant, which can, on the one hand, exhibit better lubrication performance on the friction pair surface, and will not have creep and leakage problems in the microgravity environment of space, and on the other hand, can further reduce the amount of lubricant used, greatly saving the cost of use.
[0024] The present invention provides an application of the gallium-based liquid metal grease lubricant described in the above technical solution in the lubrication field of the space atomic oxygen irradiation environment. The gallium-based liquid metal grease lubricant mainly provides lubrication by the gallium-rich film generated by adsorption on the friction interface, and the gallium-based liquid metal grease lubricant is applied in the space atomic oxygen irradiation environment, and the friction coefficient and wear rate of the friction pair will not change significantly compared with before irradiation, that is, it will not fail in the space atomic oxygen irradiation environment.
[0025] The present invention also provides a lubrication system suitable for space atomic oxygen irradiation environment, comprising a gallium-based liquid metal grease lubricant and a friction pair; the material of the friction pair comprises an iron-based alloy, a nickel-based alloy or a titanium alloy. For other friction pair materials, the gallium-based liquid metal grease lubricant will not corrode the above friction pair materials. Furthermore, the oxidation of the gallium-based liquid metal caused by atomic oxygen irradiation will further accelerate the corrosion of other friction pair materials, while the gallium-based liquid metal grease lubricant will not corrode the above friction pair materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The friction coefficient curve of the 9Cr18 steel ball / 9Cr18 steel disc friction pair lubricated by the gallium-based liquid metal grease lubricant described in Example 1 before and after atomic oxygen irradiation and the wear rate of the 9Cr18 steel disc;
[0027] Figure 2 The actual pictures of the gallium-based liquid metal, the incompletely oxidized gallium-based liquid metal and the fully oxidized gallium-based liquid metal grease lubricant described in Example 1 and their spreading conditions on the surface of a 9Cr18 steel disc;
[0028] Figure 3 The viscosity variation curves of the fully oxidized gallium-based liquid metal grease lubricant and the incompletely oxidized gallium-based liquid metal as a function of shear rate and the viscosity value when the shear rate approaches 0 described in Example 1;
[0029] Figure 4The friction coefficient curve of the 9Cr18 steel ball / CuSn6 copper alloy disk friction pair lubricated by the gallium-based liquid metal grease lubricant described in Comparative Example 1 before and after atomic oxygen irradiation and the wear rate of the CuSn6 copper alloy disk;
[0030] Figure 5 The friction coefficient curve of the 9Cr18 steel ball / 9Cr18 steel disc friction pair lubricated by the space lubricant polyalphaolefin (PAO) described in Comparative Example 3 before and after atomic oxygen irradiation and the wear rate of the 9Cr18 steel disc. DETAILED DESCRIPTION
[0031] The present invention provides a gallium-based liquid metal grease lubricant. The gallium-based liquid metal used to prepare the gallium-based liquid metal grease lubricant comprises, by weight percentage, 70-72% gallium, 14-16% indium, 12-14% tin and 0.8-1.2% zinc.
[0032] The viscosity of the gallium-based liquid metal grease lubricant is ≥6.0×10 6 mPa·s.
[0033] In the present invention, the elements of the gallium-based liquid metal used to prepare the gallium-based liquid metal grease lubricant more preferably include 71% gallium, 15% indium, 13% tin and 1% zinc, or include 71.5% gallium, 14% indium, 13.3% tin and 1.2% zinc, or include 70% gallium, 15% indium, 13.9% tin and 1.1% zinc, according to the mass percentage content.
[0034] In the present invention, the gallium-based liquid metal grease lubricant can, on the one hand, exhibit better lubrication performance on the friction pair surface and will not have creep and leakage problems in the microgravity environment of space; on the other hand, it can further reduce the amount of lubricant used and greatly save the cost of use.
[0035] The present invention also provides a method for preparing the gallium-based liquid metal grease lubricant described in the above technical solution, comprising the following steps:
[0036] After mixing the metal elements for preparing the gallium-based liquid metal grease lubricant, smelting the mixture in a protective atmosphere to obtain the gallium-based liquid metal;
[0037] The gallium-based liquid metal is stirred in an atmospheric environment to obtain the gallium-based liquid metal grease lubricant.
[0038] The present invention mixes metal elements for preparing the gallium-based liquid metal grease lubricant, and then performs smelting treatment in a protective atmosphere to obtain the gallium-based liquid metal.
[0039] In the present invention, the metal element for preparing the gallium-based liquid metal is preferably gallium metal element, indium metal element, tin metal element and zinc metal element; the gallium metal element is preferably a gallium block, the indium metal element is preferably an indium wire with a length of 1 to 3 mm, and the diameter of the indium wire is preferably 1 mm; the tin metal element is preferably a tin wire with a length of 1 to 3 mm, and the diameter of the tin wire is preferably 1 mm; the zinc metal element is preferably a zinc wire with a length of 1 to 3 mm, and the diameter of the zinc wire is preferably 1 mm. In the present invention, the purity of the gallium metal element, the indium metal element, the tin metal element and the zinc metal element is preferably greater than 99.99%.
[0040] In the present invention, the mixing preferably includes melting the gallium metal element and mixing it with indium metal element, tin metal element and zinc metal element. In the present invention, the melting preferably includes placing the container containing the gallium block into hot water for melting. The present invention does not have any special restrictions on the temperature of the hot water, as long as it is greater than the melting point of the gallium metal element.
[0041] In the present invention, the protective atmosphere is preferably an argon atmosphere.
[0042] In the present invention, the temperature of the smelting treatment is preferably 500-600°C, more preferably 500-550°C; the holding time is preferably 1.5-2h, more preferably 1.6-1.8h. In the present invention, the smelting treatment is preferably carried out by placing the mixed mixture in an alumina crucible and then placing the alumina crucible in an argon protected tubular furnace.
[0043] After the smelting process is completed, the present invention also preferably includes cooling. The present invention has no special limitation on the cooling process, and the cooling process can be performed using a process well known to those skilled in the art. In an embodiment of the present invention, the cooling can be furnace cooling.
[0044] After obtaining the gallium-based liquid metal, the present invention stirs the gallium-based liquid metal in an atmospheric environment to obtain the gallium-based liquid metal grease lubricant.
[0045] In the present invention, the stirring speed is preferably 200-600 rpm, more preferably 400-600 rpm; the temperature is preferably 20-80°C, more preferably 30-60°C. The present invention does not have any special restrictions on the stirring time, and the time known to those skilled in the art is used to ensure that the viscosity value is greater than or equal to 6.0×10 6 mPa·s gallium-based liquid metal grease lubricant can be used.
[0046] The present invention also provides an application of a gallium-based liquid metal grease lubricant in the lubrication field of a space atomic oxygen irradiation environment.
[0047] The present invention also provides a lubrication system suitable for space atomic oxygen irradiation environment, including a gallium-based liquid metal grease lubricant and a friction pair;
[0048] The material of the friction pair includes iron-based alloy, nickel-based alloy or titanium alloy.
[0049] In the present invention, the material of the friction pair includes an iron-based alloy, a nickel-based alloy or a titanium alloy; the iron-based alloy preferably includes 9Cr18; the nickel-based alloy preferably includes Inconel718; the titanium alloy preferably includes TC4. In an embodiment of the present invention, the material of the friction pair can be 9Cr18 steel / 9Cr18 steel (the upper friction pair is a 9Cr18 steel ball, and the lower friction pair is a 9Cr18 steel disk), 9Cr18 steel / Inconel718 nickel-based alloy (the upper friction pair is a 9Cr18 steel ball, and the lower friction pair is an Inconel718 nickel-based alloy disk) or 9Cr18 steel / TC4 titanium alloy (the upper friction pair is a 9Cr18 steel ball, and the lower friction pair is a TC4 titanium alloy disk).
[0050] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Example 1
[0052] A container containing a 99.99% pure gallium block is placed in hot water to melt the gallium block. Indium wire, tin wire and zinc wire with a purity of 99.99% and a diameter of 1 mm are cut into short wires with a length of 1 to 3 mm and weighed according to a mass ratio of 71:15:13:1. The metal elements are mixed and smelted in an argon atmosphere at a temperature of 500°C for 1.6 hours. After cooling to room temperature with the furnace, the gallium-based liquid metal Ga is sealed for standby use. 71 In 15 Sn 13 Zn1.
[0053] The gallium-based liquid metal was then stirred with a magnetic stirrer in an atmospheric environment at a stirring speed of 550 rpm, a stirring temperature of 25 °C, and a stirring time of 0.5 h to obtain a viscosity of 6.6 × 10 6 mPa·s gallium-based liquid metal grease lubricant (denoted as Ga 71 In 15 Sn 13 Zn1-Grease).
[0054] The friction pair material lubricated by the gallium-based liquid metal grease lubricant is 9Cr18 steel / 9Cr18 steel. The upper friction pair is a 9Cr18 steel ball with a diameter of 6 mm, and the lower friction pair is a 9Cr18 steel disk with a diameter of 30 mm and a height of 8 mm. The friction coefficient of the 9Cr18 steel / 9Cr18 steel friction pair lubricated by the gallium-based liquid metal grease lubricant before and after atomic oxygen irradiation and the wear rate of the 9Cr18 steel disk are investigated.
[0055] Example 2
[0056] A container containing a 99.99% pure gallium block is placed in hot water to melt the gallium block. Indium wire, tin wire and zinc wire with a purity of 99.99% and a diameter of 1 mm are cut into short wires with a length of 1 to 3 mm and weighed according to a mass ratio of 71.5:14:13.3:1.2. The metal elements are mixed and smelted in an argon atmosphere at a temperature of 520°C for 1.7 hours. After cooling to room temperature with the furnace, the gallium-based liquid metal Ga is sealed for standby use. 71.5 In 14 Sn 13.3 Zn 1.2 .
[0057] The gallium-based liquid metal was then stirred with a magnetic stirrer in an atmospheric environment at a stirring speed of 580 rpm, a stirring temperature of 28 °C, and a time of 0.55 h to obtain a viscosity of 6.8 × 10 6 mPa·s gallium-based liquid metal grease lubricant (denoted as Ga 71.5 In 14 Sn 13.3 Zn 1.2 -Grease).
[0058] The friction pair lubricated by gallium-based liquid metal grease lubricant is made of 9Cr18 steel / Inconel718 nickel-based alloy. The upper friction pair is a 9Cr18 steel ball with a diameter of 6 mm, and the lower friction pair is an Inconel718 nickel-based alloy disk with a diameter of 30 mm and a height of 8 mm. The friction coefficient of the 9Cr18 steel / Inconel718 nickel-based alloy friction pair and the wear rate of the Inconel718 nickel-based alloy disk are investigated.
[0059] Example 3
[0060] A container containing a 99.99% pure gallium block is placed in hot water to melt the gallium block. Indium wire, tin wire and zinc wire with a purity of 99.99% and a diameter of 1 mm are cut into short wires with a length of 1 to 3 mm and weighed according to a mass ratio of 70:15:13.9:1.1. The metal elements are mixed and smelted in an argon atmosphere at a temperature of 550°C for 1.8 hours. After cooling to room temperature with the furnace, the mixture is sealed for standby use to obtain gallium-based liquid metal Ga 70 In15 Sn 13.9 Zn 1.1 .
[0061] Then the gallium-based liquid metal was stirred with a magnetic stirrer in an atmospheric environment at a stirring speed of 600 rpm, a stirring temperature of 30 °C, and a time of 0.52 h to obtain a viscosity of 6.7 × 10 6 mPa·s gallium-based liquid metal grease lubricant (denoted as Ga 70 In 15 Sn 13.9 Zn 1.1 -Grease).
[0062] The friction pair lubricated by gallium-based liquid metal grease is made of 9Cr18 steel / TC4 titanium alloy. The upper friction pair is a 9Cr18 steel ball with a diameter of 6 mm, and the lower friction pair is a TC4 titanium alloy disk with a diameter of 30 mm and a height of 8 mm. The friction coefficient of the 9Cr18 steel / TC4 titanium alloy friction pair and the wear rate of the TC4 titanium alloy disk are investigated.
[0063] Comparative Example 1
[0064] The difference from Example 1 is that the friction pair material lubricated by the gallium-based liquid metal grease lubricant is 9Cr18 steel / CuSn6 copper alloy. The upper friction pair is a 9Cr18 steel ball with a diameter of 6 mm, and the lower friction pair is a CuSn6 copper alloy disk with a diameter of 30 mm and a height of 8 mm. The friction coefficient of the 9Cr18 steel / CuSn6 copper alloy friction pair and the wear rate of the CuSn6 copper alloy disk are investigated.
[0065] Comparative Example 2
[0066] The difference from Example 1 is that the friction pair material lubricated by the gallium-based liquid metal grease lubricant is 9Cr18 steel / Al7075 aluminum alloy. The upper friction pair is a 9Cr18 steel ball with a diameter of 6 mm, and the lower friction pair is an Al7075 aluminum alloy disk with a diameter of 30 mm and a height of 8 mm. The friction coefficient of the 9Cr18 steel / Al7075 aluminum alloy friction pair and the wear rate of the Al7075 aluminum alloy disk are investigated.
[0067] Comparative Example 3
[0068] Space lubricant polyalphaolefin (PAO) was used as lubricant, and the friction pair material was 9Cr18 steel / 9Cr18 steel. The upper friction pair was a 9Cr18 steel ball with a diameter of 6 mm, and the lower friction pair was a 9Cr18 steel disc with a diameter of 30 mm and a height of 8 mm. The friction coefficient of the 9Cr18 steel / 9Cr18 steel friction pair and the wear rate of the 9Cr18 steel disc were investigated.
[0069] Comparative Example 4
[0070] Space lubricant perfluoropolyether (PFPE) was used as lubricant, and the friction pair material was 9Cr18 steel / 9Cr18 steel. The upper friction pair was a 9Cr18 steel ball with a diameter of 6 mm, and the lower friction pair was a 9Cr18 steel disk with a diameter of 30 mm and a height of 8 mm. The friction coefficient of the 9Cr18 steel / 9Cr18 steel friction pair and the wear rate of the 9Cr18 steel disk were investigated.
[0071] Test Case
[0072] The lubrication performance of the gallium-based liquid metal grease lubricants of Examples 1 to 3 and the lubricants of Comparative Examples 1 to 3 was tested before and after atomic oxygen irradiation. The specific experimental conditions are as follows:
[0073] 1) Lubricant performance test before atomic oxygen irradiation: Spread a certain thickness of lubricant on the surface of the lower friction pair, and use a vacuum friction and wear tester to test the lubricating behavior of the lubricant before atomic oxygen irradiation. The test parameters are: vacuum degree 3.0×10 -2 Pa, normal load is 5N, chassis speed is 200rpm, friction time is 1h, and friction radius is 5mm. The friction coefficient of the friction pair is automatically recorded by the vacuum friction and wear tester. The wear volume of the disk is measured by a non-contact surface profiler, and the wear rate is calculated as the wear volume divided by the normal load and sliding distance.
[0074] 2) Lubricant performance test after atomic oxygen irradiation: A certain thickness of lubricant is spread on the friction pair surface, and the lubricant is first irradiated with atomic oxygen using a simulated space atomic oxygen irradiation device. The vacuum degree of the simulated irradiation device is 3.0×10 - 2 Pa, the average impact energy of atomic oxygen irradiation is 5.0 eV, and the flux is 18×10 15 atoms / (cm 2 ·s), the irradiation time is 1 hour, and the corresponding atomic oxygen irradiation dose is 6.48×10 19 atoms / cm 2 Then, the lubrication behavior of the lubricant after atomic oxygen irradiation was tested using a vacuum friction and wear tester. The test parameters were: vacuum degree 3.0×10 -2 Pa, normal load is 5N, chassis speed is 200rpm, friction time is 1h, and friction radius is 5mm. The friction coefficient of the friction pair is automatically recorded by the vacuum friction and wear tester. The wear volume of the disk is measured by a non-contact surface profiler, and the wear rate is calculated as the wear volume divided by the normal load and sliding distance.
[0075] The test results are shown in Table 1 and Figures 1 to 5 As shown, Figure 1The friction coefficient curve (a) and the wear rate (b) of the 9Cr18 steel disk lubricated by the gallium-based liquid metal grease lubricant in Example 1 before and after atomic oxygen irradiation are shown in FIG. Figure 1 It can be seen that the average friction coefficient of the gallium-based liquid metal grease lubricant lubricating the 9Cr18 steel / 9Cr18 steel friction pair before atomic oxygen irradiation is 0.26, and the wear rate of the 9Cr18 steel disk is (1.43±0.21)×10 -6 mm 3 / N·m; the average friction coefficient of the lubricated 9Cr18 steel / 9Cr18 steel friction pair after atomic oxygen irradiation is 0.30, and the wear rate of the 9Cr18 steel disk is (2.99±1.05)×10 -6 mm 3 / N·m. Atomic oxygen irradiation has little effect on the lubrication effect of gallium-based liquid metal grease lubricant on 9Cr18 steel / 9Cr18 steel friction pair. The average friction coefficient has not increased significantly, and the wear rate remains at 10 -6 mm 3 / N·m order of magnitude.
[0076] Figure 2 The gallium-based liquid metal and the incompletely oxidized gallium-based liquid metal grease lubricant described in Example 1 (the condition of incomplete oxidation is that the viscosity value is less than 6.0×10 6 mPa·s) and fully oxidized gallium-based liquid metal grease lubricant (the condition for full oxidation is that the viscosity value is greater than or equal to 6.0×10 6 mPa·s) and its spreading on the surface of 9Cr18 steel disc. Figure 2 It can be seen that the gallium-based liquid metal presents a metallic luster, has fluidity, and does not wet the surface of the 9Cr18 steel disc; the gallium-based liquid metal that is not fully oxidized is composed of solid gallium oxide, indium / tin precipitates and liquid gallium-based liquid metal, and has a certain fluidity. The wettability on the surface of the 9Cr18 steel disc is improved to a certain extent, but due to the presence of gallium-based liquid metal, it cannot completely wet the 9Cr18 steel; and the fully oxidized gallium-based liquid metal grease lubricant is viscous, with greatly increased viscosity, and loses fluidity. It is composed of a large amount of gallium oxide, indium / tin precipitates and a small amount of gallium-based liquid metal wrapped inside, and can completely wet the 9Cr18 steel. The fully oxidized gallium-based liquid metal grease lubricant can, on the one hand, show better lubrication performance on the friction pair surface, and will not have the problem of creeping and leakage in the microgravity environment of space. On the other hand, it can further reduce the amount of lubricant used, greatly saving the cost of use.
[0077] Figure 3The viscosity variation curves of the fully oxidized gallium-based liquid metal grease lubricant and the incompletely oxidized gallium-based liquid metal as a function of shear rate (a) and the viscosity value when the shear rate approaches 0 (b) described in Example 1 are shown. Figure 3 It can be seen that the viscosity of the fully oxidized gallium-based liquid metal grease lubricant and the incompletely oxidized gallium-based liquid metal both have shear thinning characteristics. The viscosity value is the largest when the shear rate approaches 0. As the shear rate increases, the viscosity gradually decreases and then tends to be stable. When the shear rate approaches 0, the viscosity of the fully oxidized gallium-based liquid metal grease lubricant is 6.6×10 6 mPa·s, which is no longer fluid; the viscosity of the incompletely oxidized gallium-based liquid metal is 9.1×10 5 mPa·s, and has certain fluidity.
[0078] Figure 4 The friction coefficient curve (a) and the wear rate (b) of the CuSn6 copper alloy disk of the 9Cr18 steel / CuSn6 copper alloy friction pair lubricated by the gallium-based liquid metal grease lubricant described in Comparative Example 1 before and after atomic oxygen irradiation are shown in Table 1. Figure 4 It can be seen that the average friction coefficient of the 9Cr18 steel / CuSn6 copper alloy friction pair lubricated by the gallium-based liquid metal grease before atomic oxygen irradiation is 0.27, and the wear rate of the CuSn6 disk is (5.17±0.91)×10 -4 mm 3 / N·m; the average friction coefficient of the lubricated 9Cr18 steel / CuSn6 copper friction pair after atomic oxygen irradiation is 0.28, and the wear rate of the CuSn6 disk is (8.37±0.43)×10 -4 mm 3 / N·m. Under the lubrication of gallium-based liquid metal grease lubricant, the wear rate of the CuSn6 copper alloy disk increased by 2 orders of magnitude compared with the wear rate of the 9Cr18 steel disk in Example 1. This is because gallium has a strong corrosive effect on copper alloy at room temperature, generating CuGa2 intermetallic compounds, and in the process of friction, there is a synergistic effect between corrosion and friction. Friction has a destructive effect on the surface of the copper alloy, which enhances the contact between gallium and copper and greatly accelerates the corrosion rate. The corrosion product CuGa2 is easy to fall off under the action of friction, and the exposed fresh copper alloy will continue to corrode, so the wear rate of the CuSn6 disk is significantly increased.
[0079] Figure 5 The friction coefficient curve (a) and the wear rate (b) of the 9Cr18 steel disc of the space lubricant polyalphaolefin (PAO) lubricated 9Cr18 steel / 9Cr18 steel disc friction pair before and after atomic oxygen irradiation described in Comparative Example 3 are shown in FIG. Figure 5It can be seen that the average friction coefficient of the 9Cr18 steel / 9Cr18 steel friction pair lubricated by polyalphaolefin (PAO) before atomic oxygen irradiation is 0.11, and the wear rate of the 9Cr18 disk is (2.74±0.54)×10 -7 mm 3 / N·m; the average friction coefficient of the 9Cr18 steel / 9Cr18 steel friction pair lubricated by polyalphaolefin (PAO) before atomic oxygen irradiation is 0.45, and the wear rate of the 9Cr18 disk is (1.43±0.33)×10 -6 mm 3 / N·m. It can be seen that after atomic oxygen irradiation, the average friction coefficient of the polyalphaolefin (PAO) lubricated 9Cr18 steel / 9Cr18 steel friction pair increased significantly, and the wear rate of the 9Cr18 disk increased by an order of magnitude. This is mainly attributed to the bond breaking and cross-linking of polyalphaolefin (PAO) molecules caused by atomic oxygen irradiation, which makes the polyalphaolefin (PAO) lubrication fail, resulting in high friction and high wear.
[0080] Table 1 Lubricating properties of the gallium-based liquid metal grease lubricants of Examples 1 to 3 and the lubricants of Comparative Examples 1 to 3 before and after atomic oxygen irradiation
[0081]
[0082] As shown in Table 1, whether the gallium-based liquid metal grease lubricant has been irradiated with atomic oxygen or not, when lubricating the friction pairs of 9Cr18 steel / 9Cr18 steel, 9Cr18 steel / Inconel718 nickel-based alloy, and 9Cr18 steel / TC4 titanium alloy, the friction coefficient and wear rate did not increase significantly, and a gallium-rich film with low shear stress was formed at the friction interface to provide lubrication. It can be seen that the lubrication system composed of gallium-based liquid metal grease lubricant and iron-based alloy, nickel-based alloy, and titanium alloy will not fail to lubricate under the action of atomic oxygen irradiation, and can be effectively used in atomic oxygen irradiation environments.
[0083] When gallium-based liquid metal grease lubricant lubricates 9Cr18 steel / CuSn6 copper alloy and 9Cr18 steel / Al7075 aluminum alloy friction pairs, gallium-based liquid metal grease lubricant will corrode copper alloy and aluminum alloy, and there is a synergistic effect between corrosion and friction during the friction process, resulting in an order of magnitude increase in the wear rate of CuSn6 and Al7075 disks. Therefore, copper alloy and aluminum alloy are not suitable for the friction pair materials of the lubrication system.
[0084] When polyalphaolefin (PAO) and perfluoropolyether (PFPE) lubricants commonly used in space lubricants are used to lubricate 9Cr18 steel / 9Cr18 steel, atomic oxygen irradiation can destroy the molecular structure of the lubricant, causing bond breaking and cross-linking, thereby causing lubrication failure, and the friction coefficient and wear rate will increase significantly. After atomic oxygen irradiation, the average friction coefficient of 9Cr18 steel / 9Cr18 steel lubricated with polyalphaolefin (PAO) increased by 309.09%, and the wear rate of 9Cr18 steel disc increased by 421.59%; after atomic oxygen irradiation, the average friction coefficient of 9Cr18 steel / 9Cr18 steel lubricated with perfluoropolyether (PFPE) increased by 183.33%, and the wear rate of 9Cr18 steel disc increased by 727.16%.
[0085] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A gallium-based liquid metal grease lubricant, characterized in that: The elements of the gallium-based liquid metal used to prepare the gallium-based liquid metal grease lubricant include 70-72% gallium, 14-16% indium, 12-14% tin and 0.8-1.2% zinc in terms of mass percentage; The viscosity of the gallium-based liquid metal grease lubricant is ≥6.0×10 6 mPa·s.
2. The gallium-based liquid metal grease lubricant according to claim 1, characterized in that: Measured by mass percentage, the elements of the gallium-based liquid metal used to prepare the gallium-based liquid metal grease lubricant include 71% gallium, 15% indium, 13% tin and 1% zinc.
3. The method for preparing the gallium-based liquid metal grease lubricant according to claim 1 or 2, characterized in that: The following steps are involved: After mixing the metal elements for preparing the gallium-based liquid metal grease lubricant, smelting the mixture in a protective atmosphere to obtain the gallium-based liquid metal; The gallium-based liquid metal is stirred in an atmospheric environment to obtain the gallium-based liquid metal grease lubricant.
4. The preparation method according to claim 3, characterized in that: The smelting process is carried out in a protective atmosphere; The protective atmosphere is argon atmosphere.
5. The preparation method according to claim 3 or 4, characterized in that: The smelting treatment is carried out at a temperature of 500 to 600° C. and for a time of 1.5 to 2 hours.
6. The preparation method according to claim 3, characterized in that: The stirring speed is 200-600 rpm, and the temperature is 20-80°C.
7. The preparation method according to claim 3, characterized in that: The metal element for preparing the gallium-based liquid metal includes a gallium block, an indium wire with a length of 1 to 3 mm, a tin wire with a length of 1 to 3 mm, and a zinc wire with a length of 1 to 3 mm; The purity of the metal element used to prepare the gallium-based liquid metal is greater than 99.99%.
8. The preparation method according to claim 3 or 7, characterized in that: The mixing comprises melting the gallium block and mixing it with an indium wire with a length of 1 to 3 mm, a tin wire with a length of 1 to 3 mm, and a zinc wire with a length of 1 to 3 mm.
9. Use of the gallium-based liquid metal grease lubricant according to claim 1 or 2 or the gallium-based liquid metal grease lubricant prepared by the preparation method according to any one of claims 3 to 8 in the field of lubrication in space atomic oxygen irradiation environments.
10. A lubrication system suitable for space atomic oxygen irradiation environment, characterized in that: including gallium-based liquid metal grease lubricant and friction pair; The material of the friction pair includes an iron-based alloy, a nickel-based alloy or a titanium alloy; The gallium-based liquid metal grease lubricant is the gallium-based liquid metal grease lubricant according to claim 1 or 2 or the gallium-based liquid metal grease lubricant prepared by the preparation method according to any one of claims 3 to 8.
Citation Information
Patent Citations
Space atomic oxygen irradiation resistant lubricant as well as preparation method and application thereof
CN117343779A
Lubricant as well as preparation method and application thereof
CN105062613A
Gallium-based liquid metal thermal interface material capable of being cured at low temperature and preparation method of gallium-based liquid metal thermal interface material
CN115232603A
Doped transition metal gallium-based liquid metal and preparation method and application thereof
CN117051298A
Solid lubricant composites
US3427244A